2016
DOI: 10.1002/lt.24608
|View full text |Cite
|
Sign up to set email alerts
|

Liver grafts procured from donors after circulatory death have no increased risk of microthrombi formation

Abstract: Microthrombi formation provoked by warm ischemia and vascular stasis is thought to increase the risk of nonanastomotic strictures (NAS) in liver grafts obtained by donation after circulatory death (DCD). Therefore, potentially harmful intraoperative thrombolytic therapy has been suggested as a preventive strategy against NAS. Here, we investigated whether there is histological evidence of microthrombi formation during graft preservation or directly after reperfusion in DCD livers and the development of NAS. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Our rationale for use of tPA, that is, the hypothesis that microthrombi form in the peribiliary capillary plexus during the DCD LT process leading to ischemic biliary stricture formation, has been challenged. Several investigators question not only the utility, but also the wisdom of tPA use in DCD LT . Vendrell et al demonstrated hyperfibrinolysis in recipients of uncontrolled DCD donor livers compared with recipients of brain dead donor livers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our rationale for use of tPA, that is, the hypothesis that microthrombi form in the peribiliary capillary plexus during the DCD LT process leading to ischemic biliary stricture formation, has been challenged. Several investigators question not only the utility, but also the wisdom of tPA use in DCD LT . Vendrell et al demonstrated hyperfibrinolysis in recipients of uncontrolled DCD donor livers compared with recipients of brain dead donor livers.…”
Section: Discussionmentioning
confidence: 99%
“…These investigators did not have access to controlled DCD donor livers, yet the uncontrolled DCD donor liver likely represents a physiologic setting vastly different from that of the controlled DCD liver, a study design weakness recognized by the authors. In that line, Verhoeven et al recently found no evidence of increased microvascular thrombosis from intrahepatic tissue samples from discarded uncontrolled DCD grafts, dismissing the rationale for use of thrombolytic agents in DCD liver transplantation. Other reports frequently cited to dispute the role of microthrombi formation in the development of biliary strictures have predominantly examined the large extrahepatic bile duct and peribiliary vasculature .…”
Section: Discussionmentioning
confidence: 99%
“…Microvascular clot with fibrin was only found in 1%‐3% of the sections evaluated. Furthermore, when the authors evaluated cDCD and donation after brain death (DBD) grafts from an earlier era, microthrombi were found at rates of 3% and 11%, respectively, and there was no association between the presence of microthrombi and the subsequent development of ITBL . Other authors have similarly studied histopathological changes associated with the appearance of ITBL after both DBD and cDCD liver transplantation in the clinical setting and have also described low rates of microvascular thrombi and no significant association between the presence of microthrombi and the development of ITBL …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when the authors evaluated cDCD and donation after brain death (DBD) grafts from an earlier era, microthrombi were found at rates of 3% and 11%, respectively, and there was no association between the presence of microthrombi and the subsequent development of ITBL. (21) Other authors have similarly studied histopathological changes associated with the appearance of ITBL after both DBD and cDCD liver transplantation in the clinical setting and have also described low rates of microvascular thrombi and no significant association between the presence of microthrombi and the development of ITBL. (17,18) Several years ago, Porte and Clavien highlighted the fact that platelet activation is reduced and coagulation altered early after death, with less stable clot formation and marked activation of the fibrinolytic system.…”
Section: Discussionmentioning
confidence: 99%
“…The team at Indiana has had a long experience of successfully using DCD livers, and decision making around patient and recipient selection may not be easily reproduced elsewhere. Despite appropriate concern about IC, more frequent use of these organs is clearly indicated in light of the outcomes reported by Mihalyov et al (1) Whether thrombolytics are indicated in this setting, because no convincing evidence of microthrombi has been found in this population, (8) remains controversial.…”
Section: See Article On Page 1198mentioning
confidence: 99%